APPRAISAL SYSTEM ON THE TEXT OF PUBLIC SERVICE ADVERTISEMENTS IN TEBING TINGGI - Rusyda Nazhirah Yunus (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This research purposes to identify the device Appraisal contained in the text of public service ads in Tebing Tinggi by applying Systemic Functional Linguistic Theory. This research has several objectives to describe the pattern of Attitude, Engagement and Graduation in the text of public service ads in Tebing Tinggi. The method of the research used the qualitative techniques of referential match. The data used comes from the public service ads board that consists of four pieces with the theme of drugs. The result of the research showed the third of Appraisal devices, they are Attitude, Engagement, and Graduation. However, the most widely device used is the Graduation. In accordance with the goal of Public Service Advertisements (PSAS) is used to provide information and persuade or encourage people to be better, thus the negative appreciation is also found in the text of PSAS in Tebing Tinggi.